Formation of hydrothermal pits and the role of seamounts in the Guatemala Basin (Equatorial East Pacific) from heat flow, seismic, and core studies. (27th January 2017) - Villinger, H. W.; Pichler, T.; Kaul, N.; Stephan, S.; Pälike, H.; Stephan, F.
Abstract: We acquired seismic and heat flow data and collected sediment cores in three areas in the Guatemala Basin (Cocos Plate, Eastern Pacific) to investigate the process by which depressions (pits) in the sedimentary cover on young oceanic crust were formed. Median heat flow of 55 mW/m 2 for the three areas is about half of the expected conductive cooling value. The heat deficit is caused by massive recharge of cold seawater into the upper crust through seamounts which is inferred from depressed heat flow in the vicinity of seamounts. Heat flow inside of pits is always elevated, in some cases up to three times (max. 300 mW/m 2 ) relative to background. None of the geochemical pore water profiles from cores inside and outside of the pits show any evidence of active fluid flow inside the pits. All three areas originated within the high productivity equatorial zone and moved northwest over the past 15 to 18 Ma. Pits found in the working areas are likely relict dissolution structures formed by diffuse hydrothermal venting in a zone of high biogenic carbonate production which were sealed when they moved north. It is likely that these pits were discharge sites of "hydrothermal siphons" where recharging seamounts could feed cold seawater via the upper crust to several discharging pits. Probably pit density on the whole Cocos Plate is similar to the three working areas and which may explain the huge heat deficit of the Cocos Plate. Key Points: Heat flow deficit on Cocos Plate. Seamount act as recharge locations for cold seawater. Hydrothermal pits are relict structures caused by hydrothermal venting.